Implementation Of The Minimum Service Standard Policy For Transportation Of People By Train On The Yogyakarta-Solo Electric Rail Train - Erifendi Churniawan; Sapto Priyanto (Jurnal Syntax Transformation, 2023)
The Minister of Transportation of the Republic of Indonesia has issued Regulation of the Minister of Transportation Number PM 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train which is a reference for infrastructure operators and / or operators of railway facilities in providing services to service users. Tidak terkecuali bagi PT. Kereta Api Indonesia (KAI) DAOP VI Yogyakarta which is the organizer of the Yogyakarta-Solo Electric Rail Train.This research is about the Implementation of the Regulation of the Minister of Transportation of the Republic of Indonesia Number 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train, by taking place at PT. Indonesian Railway DAOP VI Yogyakarta. This research method is normative legal research, which uses key informants as research subjects, to analyze the development of information and its sources, then the sampling technique used is purposive sampling. The population in the study was all management and employees at PT. Kereta Api Indonesia DAOP VI Yogyakarta, while the sample used was only partly from the management and employees of PT. Indonesian Railway DAOP VI Yogyakarta dimulai dari arahan key informan. The results of the study are expected to inform that the implementation of the Ministerial Regulation has been implemented by the railway operator, namely PT. Kereta Api Indonesia DAOP VI Yogyakarta properly and correctly as stated in the provisions of the Regulation of the Minister of Transportation of the Republic of Indonesia Number 63 of 2019.